PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBASIS FLIPBOOK TEMA 6 SUBTEMA 1 AKU DAN CITA-CITAKU - Rizkia Innaya Putri; Sumardi; Nita Karmila (STKIP Subang, 2022)
Rizkia Innaya Putri, 037118110, Development of Digital Comic Flipbook-Based Media, Theme 6: My Aspiration, Sub-theme 1: My Learning Aspiration and I, 1. Learning media are essential for getting students' attention in teaching and learning activities. Therefore, it is necessary to develop learning media. This research intended to develop a digital comic learning media product based on flipbook Theme 6: My Aspiration, Sub-theme 1: My Learning Aspiration and I 1. This study employed Research and Development (R&D) method, applying the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. This research started with a necessities analysis to determine the initial necessary, design learning media, develop learning media and conduct validation tests on media experts, linguists and material experts; subsequently, the implementation conducted a limited basis to 35 class IV students. The study's findings indicated that the developed Digital Comic Flipbook-Based Media had a highly feasible category. This was based on the percentage of media experts at 92%, linguists at 100%, material experts at 86% and student responses with an average acquisition at 98%. Based on the results of this study, it can be summarised that the Digital Comic Flipbook-Based Media developed was feasible to be utilised as a learning aid instrument. Keywords: Digital comic learning media, Flip-book, Theme 6: My Aspiration, Sub-theme 1: My Aspiration and I